Is parity a risk factor for excessive weight gain during pregnancy and postpartum weight retention? A systematic review and meta‐analysis. (17th May 2017) - Hill, B.; Bergmeier, H.; McPhie, S.; Fuller‐Tyszkiewicz, M.; Teede, H.; Forster, D.; Spiliotis, B. E.; Hills, A. P.; Skouteris, H.
Summary: The aim of this study was to systematically review and meta‐analyse the associations between parity, pre‐pregnancy body mass index (BMI), gestational weight gain (GWG) and, when included, postpartum weight retention (PPWR). Papers reporting associations between parity and BMI and/or GWG in adult women were eligible: 2, 195 papers were identified, and 41 longitudinal studies were included in the narrative synthesis; 17 studies were included in a meta‐analysis. Findings indicated that parity was associated positively with pre‐pregnancy BMI. In contrast, the role of parity in GWG was less clear; both positive and negative relationships were reported across studies. Parity was not associated directly with PPWR. This pattern of results was supported by our meta‐analysis with the only significant association between parity and pre‐pregnancy BMI. Overall, parity was associated with higher pre‐pregnancy BMI; however, the role of parity in GWG and PPWR remains unclear, and it is likely that its influence is indirect and complex. Further research to better understand the contribution of parity to maternal obesity is warranted.